Study on the implementation and development of an ECVET system for initial vocational education and training : ECVET reflector. Final report - Fietz, Gabriele [Verfasser]; Reglin, Thomas [Verfasser]; Le Mouillour, Isabelle [Verfasser] (My University, 2007)
The ECVET reflector study was carried on behalf of the European Commission between December 2005 and February 2007, shortly before the ECVET consultation phase. It is embedded in the general objectives of the European Commission and Parliament on enhancing mobility of apprentices (both young people and adults) within VET. The study mandate was to analyse the relationships between the features of the European credit system for vocational education and training (ECVET) and the existing regulations and practices of assessment, validation and certification as well as accumulation and transfer of learning outcomes in the national and/or qualifications and VET systems in Europe. The results presented in this report rely on the analysis of documents selected by national experts and compiled in a database containing 417 documents. The scope of the study and its focus on actual development required a regional survey design and the active participation of 55 regional experts who carried out a total of 186 standardised interviews in 32 countries. It evaluates both the status quo and the dynamics revealed by VET systems (which in many countries are indeed considerable) to identify both synergy effects and obstacles which may occur while introducing ECVET. (BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Europäisches Leistungspunktesystem; Berufsbildung; Europa